Effects of Early Fruiting Branch Removal on Physiological Traits of Leaves Related to Premature Senescence, Yield, and Fiber Quality of Transgenic Bt Cotton. Issue 2 (1st March 2018) - Zhai, Lichao; Zhang, Yongjiang; Li, Cundong; Zhai, Lifang; Liu, Liantao; Sun, Hongchun
Abstract : Cotton ( Gossypium hirsutum L.) is characterized by an indeterminate growth habit, and removal of early fruiting forms often elicits compensatory growth. However, no consensus has been reached on the response of cotton to removal of fruiting forms. We conducted field experiments in 2010 and 2011 with four different early fruiting branch removal treatments (CK, untreated control; R1, removal of one basal fruiting branch; R2, removal of two basal fruiting branches; and R3, removal of three basal fruiting branches) to explore the effects of removing early fruiting branches on premature senescence, yield, and fiber quality of cotton planted on two planting dates. Our results showed that removing early fruiting branches delayed premature senescence of cotton in terms of chlorophyll content, malondialdehyde content, and peroxidase and superoxide dismutase activities at the mid‐late growth stage, especially with R1 and R2 treatments for early‐planted cotton. Removing early fruiting branches increased the leaf area index, leaf area duration, and net assimilation rate compared with untreated plants, which further increased the dry matter accumulation, yield, and some yield components, and significant differences were observed for the R1 and R2 treatments, especially for early‐planted cotton. However, no significant beneficial effects were observed on fiber quality after removing early fruiting branches. In conclusion, removing one or two early fruiting branches delayed premature senescence and improved yield in early‐planted cotton but did not affect fiber quality. Therefore, it could be an effective practice to incorporate into cotton production.